Designing a novel 3D nanofibrous scaffold based on nanoalloy AuAg NPs (AuAg@ PAN NFs) for osteogenic differentiation of human adipose derived mesenchymal stem cells (hADMSCs). (15th March 2022) - Kh. Kara, Gheffar; Tadjarodi, Azadeh; Kehtari, Mousa
Graphical abstract: The schematic representation shows the synthesis steps of a new electrospun scaffold, which consists of two compatible components (polyacrylonitrile polymer matrix and AuAg NPs alloy nanoparticles) without any other additives. Surface properties, mechanical stability and hydrophilic scaffold are the advantages of the prepared scaffold that made it a suitable environment for well cell adhesion and differentiation of osteoblasts on their surface. Highlights: A facial way is pursued to design an alloyed nanofibrous scaffold of AuAg@ PAN NFs. AuAg NPs ensure a positive role in fortifying the structural properties of PAN. The scaffold showed good mechanical stability and wetting behavior. The AAP NFs exhibited excellent performance in inducing the osteogenic process. AuAg NPs hold great promise in the future of bone scaffolds. Abstract: The present study applied a new strategy to modify the surface properties of a polymeric matrix with the aim of forming an osteogenic scaffold with a stable structure and better osteo-inductive potential. To this purpose, we applied appropriate electrospinning conditions to design the nanofibrous scaffold of AuAg@ polyacrylonitrile (P) nanofibers (AAP NFs), based on incorporation of the AuAg nanoparticles (AA NPs) which were prepared by ultrasound irradiation, with an electrospinning solution of polyacrylonitrile. This study has combined structural properties (crystalline, morphology, roughness) and surficial properties (mechanical and wettability) of fibrous samples, in order to elucidate the role of surface modification and formation of a stable fibrous scaffold in osteogenic differentiation. The XRD and FT-IR findings showed that the all crystalline properties of hexagonal system and the intensity of related IR-bands were changed. This modification caused the removal a smooth outer fiber layer of the P NFs and the creation of chunky shapes of AA NPs on the surface of the corresponding fibrous sample, which were confirmed by enhancing Ra values. The nanofibrous scaffold with 2% AA NPs disclosed the best mechanical performance and wettability. Finally, we showed that AAP NFs, not only improved cell adhesion, but also induced osteogenic differentiation of human adipose derived mesenchymal stem cells(hADMSCs) more efficiently than P NFs and tissue culture plates (TCPs).